Meishu, travels in Chinese art (Chicago, Ill Home Vision, 1988)
This program explores China's erratic and invariably difficult contacts with other cultures and ideologies, caused by both natural and cultural barriers, and how this isolation has allowed China to develop her own great and distinctive traditions in art. Edmund Capon looks at China's cultural evolution through 2000 years of trading and commercial contacts and considers some of the ideological influences that entered the country from the outside world.
VHS format.
Producer/director, Stafford Garner ; writers, Edmund Capon, Stafford Garner ; writers, Edmund Capon, Stafford Garner ; editor, David Maitland ; music, Cameron Allan.
Edmund Capon
Keywords: Art -- Chinese -- History; China -- Foreign influences; China -- Civilization